2011
DOI: 10.1186/1746-6148-7-35
|View full text |Cite
|
Sign up to set email alerts
|

A novel point mutation within the EDA gene causes an exon dropping in mature RNA in Holstein Friesian cattle breed affected by X-linked anhidrotic ectodermal dysplasia

Abstract: BackgroundX-linked anhidrotic ectodermal dysplasia is a disorder characterized by abnormal development of tissues and organs of ectodermal origin caused by mutations in the EDA gene. The bovine EDA gene encodes the ectodysplasin A, a membrane protein expressed in keratinocytes, hair follicles and sweat glands, which is involved in the interactions between cell and cell and/or cell and matrix. Four mutations causing ectodermal dysplasia in cattle have been described so far.ResultsWe identified a new single nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…Studies reported a QTL in the PAPD7 , ICE1 , and LOC101907249 gene regions associated with percentage abnormal sperm in Holstein bulls [ 34 ] and calving ease in Angus breed cows [ 33 ]. The EDARADD gene participates in cell differentiation and mutations in this gene can result in abnormal development of tissues and organs of ectodermal origin [ 35 ]. In this region, a QTL associated with pregnancy rate trait have been reported by Boichard et al [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported a QTL in the PAPD7 , ICE1 , and LOC101907249 gene regions associated with percentage abnormal sperm in Holstein bulls [ 34 ] and calving ease in Angus breed cows [ 33 ]. The EDARADD gene participates in cell differentiation and mutations in this gene can result in abnormal development of tissues and organs of ectodermal origin [ 35 ]. In this region, a QTL associated with pregnancy rate trait have been reported by Boichard et al [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations affecting the Eda pathway are known in medaka [ 13 ], zebrafish [ 14 ], mouse [ 4 , 6 , 8 ], cattle [ 15 - 18 ], dog [ 19 ], and human [ 3 , 5 , 6 ]. Of them, the mouse mutants have been widely characterized as a model organism of HED.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in some of the genes in the Eda pathway have been identified in various species, such as medaka [ 13 ], zebrafish [ 14 ], cattle [ 15 - 18 ], and dog [ 19 ]. Analyses of these mutations showed critical roles of the Eda pathway in the development of epithelial appendages, as well as in morphological evolution.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to ameliorate or abolish congenital defects of HED using short-term treatment with recombinant ectodysplasin was first demonstrated in Tabby mice and refined in a canine model, leading to successful treatment of human fetuses [ 16 , 17 , 18 , 19 ]. To date, there are eight reported pathogenic variants of the bovine EDA gene that, result in an ECTD1-like disease (OMIA 000543-9913) [ 8 , 9 , 10 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. They are potentially lethal since affected cattle are ill-thrifty due to oligodontia and the heightened risk for pneumonia and hypothermia [ 20 , 21 , 27 ].…”
Section: Introductionmentioning
confidence: 99%